Targeted Nanobubbles Carrying Indocyanine Green for Ultrasound, Photoacoustic and Fluorescence Imaging of Prostate Cancer - Wang, Yixuan (Int J Nanomedicine, 2020)
OBJECTIVE: To construct prostate-specific membrane antigen (PSMA)-targeting, indocyanine green (ICG)-loaded nanobubbles (NBs) for multimodal (ultrasound, photoacoustic and fluorescence) imaging of prostate cancer. METHODS: The mechanical oscillation method was used to prepare ICG-loaded photoacoustic NBs (ICG NBs). Then, PSMA-binding peptides were connected to the surface of ICG NBs using the biotin–avidin method to make targeted photoacoustic NBs, namely, PSMAP/ICG NBs. Their particle sizes, zeta potentials, and in vitro ultrasound, photoacoustic and fluorescence imaging were examined. Confocal laser scanning microscopy and flow cytometry were used to detect the binding ability of the PSMAP/ICG NBs to PSMA-positive LNCaP cells, C4-2 cells, and PSMA-negative PC-3 cells. The multimodal imaging effects of PSMAP/ICG NBs and ICG NBs were compared in nude mouse tumor xenografts. RESULTS: The particle size of the PSMAP/ICG NBs was approximately 457.7 nm, and the zeta potential was approximately −23.5 mV. Both confocal laser scanning microscopy and flow cytometry confirmed that the PSMAP/ICG NBs could specifically bind to both LNCaP and C4-2 cells, but they rarely bound to PC-3 cells. The ultrasound, photoacoustic and fluorescence imaging intensities of the PSMAP/ICG NBs in vitro positively correlated with their concentrations. The ultrasound and photoacoustic imaging effects of the PSMAP/ICG NBs in LNCaP and C4-2 tumor xenografts were significantly enhanced compared with those in PC-3 tumor xenografts, which were characterized by a significantly increased duration of ultrasound enhancement and heightened photoacoustic signal intensity (P < 0.05). Fluorescence imaging showed that PSMAP/ICG NBs could accumulate in LNCaP and C4-2 tumor xenografts for a relatively long period. CONCLUSION: The targeted photoacoustic nanobubbles prepared in this study can specifically bind to PSMA-positive prostate cancer cells and have the ability to enhance ultrasound, photoacoustic and fluorescence imaging of PSMA-positive tumor xenografts. Photoacoustic imaging could visually display the intensity of the red photoacoustic signal in the tumor region, providing a more intuitive imaging modality for targeted molecular imaging. This study presents a potential multimodal contrast agent for the accurate diagnosis and assessment of prostate cancer.